Fever and infections during pregnancy and psychosis-like experiences in the offspring at age 11. A prospective study within the Danish National Birth Cohort. Issue 3 (24th July 2017) - Dreier, J. W.; Berg-Beckhoff, G.; Andersen, A. M. N.; Susser, E.; Nordentoft, M.; Strandberg-Larsen, K.
Abstract : Background: Maternal exposures to fever and infections in pregnancy have been linked to subsequent psychiatric morbidity in the child. This study examined whether fever and common infections in pregnancy were associated with psychosis-like experiences (PLEs) in the child. Methods: A longitudinal study of 46 184 children who participated in the 11-year follow-up of the Danish National Birth Cohort was conducted. Pregnant women were enrolled between 1996 and 2002 and information on fever, genitourinary infections, respiratory tract infection, and influenza-like illness during pregnancy was prospectively collected in two interviews during pregnancy. PLEs were assessed using the seven-item Adolescent Psychotic-Like Symptom Screener in a web-based questionnaire completed by the children themselves at age 11. Results: PLEs were reported among 11% of the children. Multinomial logistic regression models with probability weights to adjust for potential selection bias due to attrition suggested that maternal fever, genitourinary infections and influenza-like illness were associated with a weak to moderate increased risk of subclinical psychosis-like symptoms in the offspring, whereas respiratory tract infections were not. No clear pattern was observed between the strengths of the associations and the timing of exposure, or the type of psychosis-like symptom. Conclusions: In this study, maternal exposures to fevers and common infections in pregnancy were generally associated with a subtle excess risk of PLEs in the child. A more pronounced association was found for influenza-like illness under an a priori definition, leaving open the possibility that certain kinds of infections may constitute important risk factors.